Improvement of conditional Cre-lox system through application of the regulatory sequences from Cowpea mosaic virus - Kopertekh, Lilya (2018)
To study the impact of regulatory sequences from Cowpea mosaic virus (CPMV) on Cre-mediated recombination rates, the cre gene was flanked by the 5′ non-translated and 3′ non-translated regions of CPMV. This cre configuration was tested by simultaneous excision of nptII selectable marker gene and heat-inducible cre recombinase gene in potato. Fusion of the cre recombinase sequence with modified regulatory sequences of CPMV increased both the excision efficiencies in primary regenerants and transmission frequencies of recombined loci to vegetative progeny as was confirmed by molecular analysis. These data might have practical implication with regard to selection of putative recombinants in vegetative progeny of potato and other clonally propagated plants as well.